Job satisfaction among elementary school teachers: A case report from Kien Giang, Vietnam - Du , Thong Nhat (Tạp chí Khoa học Trường Đại học Sư phạm Thành phố Hồ Chí Minh, 2019)
This article presented the findings of a study in which the Teachers’ Job Satisfaction Scale (JSS) was adapted to Vietnamese educational context in order to examine the Job Satisfaction as perceived by 655 Vietnamese elementary school teachers in Kien Giang province in the 2014-2015 school year. The findings reported that the elementary school teachers were moderately satisfied with their job. There were significant differences in the perceptions of elementary school teachers about the dimensions of job satisfaction, according to their gender, school size, and school location.